Variabel Penentu Produktivitas Amil dan Kinerja Penyaluran Zakat dan Infaq pada Baznas Kabupaten di Provinsi Jawa Timur - Zakiyyah Ilma Ahmad (Universitas Jember, 2020)
This study aims to determine how the performance of BAZNAS Jawa Timur in zakat, infaq, and shadaqah distribution. This type of research is explanatory research, namely research that explains the relationship of the influence of independent variables on the dependent variable through the hypothesis test. Type of data used in this study is secondary data in the form of financial data sourced from financial statements related to the variables studied. Data source obtained by BAZNAS financial report in East Java Province. The results of this study are the zakat collection variable and infaq collection variable does not affect the amil productivity. Amil productivity does not affect the performance of zakat distribution and infaq distribution performance. All hypotheses are rejected. Keywords: Zakat, Infaq, Shadaqah, Collecting, Amil Productivity, Distribution Performance.